If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = xcos(x) Multiply cosx * x y = cosx2 Solving y = cosx2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = cosx2
| 2+2=8b | | 2x-5(x-5)=-4+3x+17 | | =2(x+y)+9x+6y | | 42=3(2-6h) | | z+8(z-4)=-4 | | 2x^2-9x-12=0 | | 77-7x=11x+19 | | 6x=24+3x | | B=58b | | 3(m+5)=39 | | S=6-3 | | c-80=36 | | X=38-(-x) | | 3(x+4)-(x+5)=x+4 | | =7+4(x+5) | | f=6q-4 | | -23b=35b | | .23x+.45=8-.32x | | 3x+-7+2x=9 | | 3x-8=5x+3 | | 18x^2-25x=-8 | | 0=-16t^2+60 | | (24)5= | | =7x+4(x+5) | | 4(x-6)+4=6x-8 | | 2r^2+18r+33=0 | | 2x+8=63 | | log(5x+70)=2 | | -55=3x+7x+5 | | =3(x+2)+5x | | 2(x-7)-1=-5(6-x) | | -1+x+x=13 |